Digital Information Ecosystems - Augey, Dominique; Alcaraz, Marina (Wiley-ISTE, 2019)
Digital information, particularly for online newsgathering and reporting, is an industry fraught with uncertainty and rapid innovation. Digital Information Ecosystems: Smart Press crosses academic knowledge with research by media groups to understand this evolution and analyze the future of the sector, including the imminent employment of bots and artificial intelligence. The book adopts an original and multidisciplinary approach to this topic: combining the science of media economics with the experience of a practicing journalist of a major daily newspaper. The result is an essential guide to the opportunities of the media to respond to a changing global digital landscape. Independent news reporting is vital in the contemporary democracy; the media must itself become a new "smart press."